Personalized nanovaccines for treating solid cancer metastases - Tang Feng; Jia Hu; Jirui Wen; Zhiyong Qian; Guowei Che; Qinghua Zhou; Lingling Zhu (Journal of Hematology & Oncology)
Abstract Cancer vaccines have garnered attention as a potential treatment for cancer metastases. Nevertheless, the clinical response rate to vaccines remains < 30%. Nanoparticles stabilize vaccines and improve antigen recognition and presentation, resulting in high tumor penetration or accumulation, effective co-distribution of drugs to the secondary lymphatic system, and adaptable antigen or adjuvant administration. Such vaccine-like nanomedicines have the ability to eradicate the primary tumors as well as to prevent or eliminate metastases. This review examines state-of-the-art nanocarriers developed to deliver tumor vaccines to metastases, including synthetic, semi-biogenic, and biogenic nanosystems. Moreover, it highlights the physical and pharmacological properties that enhance their anti-metastasis efficiency. This review also addresses the combination of nanovaccines with cancer immunotherapy to target various steps in the metastatic cascade, drawing insights from preclinical and clinical studies. The review concludes with a critical analysis of the challenges and frameworks linked to the clinical translation of cancer nanovaccines.